Expression of PAX2 and Renal Cell Carcinoma Antigen in Mucoepidermoid Carcinoma - Liu, MD, PhD, Yunguang; Cheney, MD, Richard T.; Omilian, PhD, Angela; Morrison, MD, Carl; Xu, MD, PhD, Bo (North American Journal of Medicine and Science, 2012)
Clear cell renal cell carcinoma (CCRCC) is the most common metastatic clear cell tumor in the head and neck. The most common primary tumor of the head and neck with clear cell morphology is mucoepidermoid carcinoma (MEC). The distinction between MEC with clear cells (CMEC) and metastatic CCRCC can be challenging in a small biopsy specimen. Expression of PAX2 and renal cell carcinoma antigen (RCCma) has been widely used to aid of diagnosis for both primary and metastatic RCC. The aim of this study is to evaluate the utility of expression of PAX2 and RCCma between CMEC and metastatic CCRCC in a clinical setting using tissue microarrays (TMAs). In primary CCRCC, the nuclear immunoreactivity for PAX2 was found in 47 of 120 cases (39%), and the membranous staining pattern for RCCma was revealed in 69 of 120 cases (58%). The immunostain profiles of metastatic RCC showed positive staining for PAX2 in 21 of 94 cases (22%) and RCCma in 19 cases (20%), respectively. Two of six cases (33%) of metastatic RCC to the head and neck region display immunoreactivity for either PAX2 or RCCma. For MEC, positive membranous and cytoplasmic staining of RCCma was found in 3 of 23 cases (13%), and diffuse cytoplasmic reactivity for PAX2 was noted in 19 cases (83%). However, none of MEC showed nuclear reactivity that is specific for PAX2. Results of our study suggest that although PAX2 and RCCma are relatively specific for CCRCC, one should be cautious when interpreting the results of RCCma and PAX2 expression in the setting of CMEC versus metastatic CCRCC, particularly in a biopsy specimen. Clinicopathologic correlation combined with histomorphology and a panel of immunohistochemical markers is essential to render correct diagnosis. [N A J Med Sci. 2012;5(4):203-207.]